Private capital flows to developing countries : the role of the domestic financial sector. - Choong, Chee Keong; Yusop, Zulkornain; Law, Siong Hook (Routledge, 2010)
The relationship between private capital flows and growth has been examined extensively in the literature, yet numerous controversies remain. This study examines the relationships among private capital flows (foreign direct investment and portfolio investment), financial development and economic performance in a panel of developing countries over the period 1983–2006, by employing generalized method of moments(GMM) panel data analysis. We find that these private capital flows have a positive impact on growth with a well-developed financial sector but have a negative effect in the presence of poor financial sector development. Moreover, foreign direct investment promotes economic growth via efficiency effect, while portfolio investment stimulates economic growth via investment effect. Hence, well-developed financial sectors are ones that are crucial for economic growth.